Práticas pedagógicas na educação infantil : o brincar na narrativa de educadoras de crianças de zero a três anos - Fontes, Naiane Libório (2017)
The present study has the main objective to understand the conceptions and the organization of pedagogical practices about the play from narratives produced by educators of children from zero to three years. Specifically, it intends to analyze the conceptions about the play of educators in the daily practices of the day care center and to characterize the practices of the play present in the actions of the educators. The study has a methodology of qualitative nature and we use meetings of studies and reflections called meetings in the search to understand what educators of children from 0 to 3 years think and do about playing. The research subjects were seven educators from three groups of children aged 0 to 3 years, members of a Municipal Infant Education Unit located in Lagarto/SE. The data were produced from observation and five study meetings about playing in Infant Education. The educators' narratives about playing were produced in the spaces of dialogues and reflections on pedagogical practice and categorized through the analysis of content. The results indicate that the play is present in the routine of the classes studied, that is, there is a time dedicated to it, but lack investments of the educators as to the forms in which it happens and of the materials available to this. The narratives of the educators show a conception of the play predominantly as a space destined to the learning of specific contents, disregarding aspects of the play related to childhood and the motivations of the child.